2018
DOI: 10.4236/ojemd.2018.85013
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuropathy and Vasculopathy; Frequency and Associated Risk Factors in Newly Diagnosed Treatment Naive Type 2 Diabetes

Abstract: Background: The prevalence of diabetes in Pakistan is 11.45%. The reported prevalence of diabetic foot ulceration in Pakistan is between 4% and 10%, with the amputation rate of 8%-21%. Peripheral neuropathy and vasculopathy are main underlying cause of diabetic foot ulcers. Methodology: It was a cross-sectional non-interventional cohort study where all newly diagnosed treatment naïve type 2 diabetic patients were enrolled. Peripheral neuropathy and vasculopathy were detected by Michigan neuropathy screening in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…In addition, the currently reported risk factors for diabetes complicated with peripheral neuropathy include vitamin D[4143] c-peptide[31], hyperlipidemia[42], alcohol intake[44], hyperglycemia[41, 42], LDL-C[29, 35, 36], BUN[22, 33] amongst others, except the duration of diabetes, age, HbA1c, DR, smoking, BMI, TC, TG. These risk factors play an important role in better explaining the causes of diabetes complicated with peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the currently reported risk factors for diabetes complicated with peripheral neuropathy include vitamin D[4143] c-peptide[31], hyperlipidemia[42], alcohol intake[44], hyperglycemia[41, 42], LDL-C[29, 35, 36], BUN[22, 33] amongst others, except the duration of diabetes, age, HbA1c, DR, smoking, BMI, TC, TG. These risk factors play an important role in better explaining the causes of diabetes complicated with peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…17 A cross-sectional study confirmed that UACR was a risk factor for peripheral neuropathy. 8 This study showed that diabetic neuropathy was associated with DPN but lacked follow-up. Our study first demonstrated that an increase in UACR was also a risk of DPN in non-DPN patients, which complemented the above studies and may provide clues for further clinical exploration of the relationship between UACR and neuropathy in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 91%
“…6 Diabetic peripheral neuropathy (DPN) can lead to neuropathic pain, which worsens the quality of life. 7 Many studies confirmed that the level of UACR, which represents one of the risk factors of early DPN, 8 was higher in patients with neuropathy as compared those without this condition. 9 The previous research of our team found that even in the normal range, UACR and the risk of DPN showed a positive correlation.…”
Section: Introductionmentioning
confidence: 98%